Capacidad bactericida de pastas experimentales anti-A. Estudio in vitro - Galvez Calla, Luis H. (2001)
All reparative process implies invigoration of the wound with the help of mainly, colagen; the infection is the most common impediment that slows this process, it can be due to bacterial invasion or decomposition of necrotic tissues which could be resolved with pure or associated natural products. It was stablished, the antimicrobial properties of "anti-A " paste after the present in vitro study carried out to prove this property and to define its best behavior, under pure conditions or associated with other natural products. 8 more frequent types of bacterias comingfirom gum frotises were isolated; 7 aerobicas: Propionibacterium, Actinomyces, Lactobacillus, Staphylococcus, haemolyticus, Streptococcus mitis, Streptococcus salivarius and Eikenella; I anaeróbico: Veillonella; which were sensitized in a means of diffusion in agar with 8 different types qf experimental pastes, among pure and associates. After 72 incubation Its, the paste based on "sangre de grado "had better antimicrobial bahavior than the other ones, so much better if they have been elaborated with pure extracts, producing bigger inhibition halo in front of the Eikenella followed by the Lactobacillus.